Porous carbon, silicon carbon negative electrode material, preparation method, pole piece and battery
Through the liquid phase impregnation of liquid asphalt liquid phase, the closed pore effect of porous carbon is achieved under low temperature conditions, and the problems of low porous carbon yield and complex process are solved, and porous carbon materials suitable for silicon carbon anode materials are obtained.
Patent Information
- Application Number
- CN202411929086.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing porous carbon yield is low and the template agent introduction and removal process is complicated, making it difficult to achieve a low-temperature porous carbon sealed pore size with good uniformity.
The closed pore effect of porous carbon is achieved under the condition of <500°C by liquid phase asphalt liquid phase impregnation, and the closed pore rate is adjusted by controlling the component content, reaction time and temperature of the asphalt.
It achieves the porous carbon with most closed pores, small diameters, and large belly pores with a gourd-shaped pore structure under low temperature conditions, which is suitable for the isolation of subsequent silane gas deposition and electrolyte, and is in conjunction with the high first-term efficiency and high capacity performance of silicon carbon anode materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a porous carbon, silicon-carbon negative electrode material, a preparation method, a pole piece and a battery. Background Art
[0002] With the rapid development of electric vehicles and renewable energy, the demand for high-performance lithium-ion batteries continues to increase. For the negative electrode, the currently widely used negative electrode materials are various carbon materials based on graphite, with a theoretical capacity of only 372mAh / g. In actual application, it is close to the theoretical capacity and it is difficult to meet higher capacity requirements. Therefore, the research on high-specific-capacity negative electrode active materials has become a general trend. Among them, the theoretical capacity of silicon materials is much higher than that of graphite carbon materials, reaching 4200 mAh / g, and the resources are relatively abundant, making it the main choice for the next generation of new negative electrode materials.
[0003] However, there is a serious expansion problem in silicon-carbon negative electrodes. The volume expansion of silicon materials during the charge and discharge process is close to 300%, which will cause a significant decrease in the overall performance of the battery. Challenged by problems such as capacity attenuation and poor cycle stability, solving this defect of silicon materials is a topic that is currently being studied at home and abroad. Among them, CVD deposition of silicon-carbon has been a technical direction with high attention and good performance in recent years. With the widespread application of porous carbon in silicon-carbon negative electrodes, many research institutions and companies have begun to promote its industrialization. The development of this field is not only of great significance to the advancement of battery technology, but also helps to promote the development of renewable energy and electric transportation. The combination of porous carbon and silicon-carbon negative electrodes opens up new possibilities for higher performance and more sustainable lithium-ion batteries, and will play a key role in the future energy storage field.
[0004] There are many methods for producing porous carbon, such as template method and activation method. The activation method mainly uses chemical reagents to react with carbon precursors under high temperature conditions to achieve the purpose of pore formation. Commonly used activation reagents include KOH, KHCO3, NaHCO3, H3PO4 and ZnCl2. In recent years, researchers have been continuously studying new preparation methods to improve the performance of porous carbon and reduce costs. For example, by adjusting the pore size and morphology of the template and optimizing the activation conditions, the directional preparation of porous carbon can be achieved. These studies provide strong support for the application of porous carbon in the field of CVD silicon anode. With the deepening of research on CVD deposited silicon anode, it is found that silicon-infiltrated porous carbon materials with rich closed pore structure and nanoscale pore size are more suitable for the requirements of CVD deposited silicon anode, and can show excellent electrochemical performance in lithium-ion batteries (LIBs). However, there are still huge challenges for the precise regulation of closed pore structure and the realization of excellent electrochemical performance at low voltage platforms.
[0005] Recent studies have shown that the closed pore structure of hard carbon materials can be significantly improved through chemical cross-linking reactions and oxygen free radical reactions. For example, during the carbonization of discarded corks, increasing the pyrolysis temperature to increase the number of closed pores and reducing the number of open pores is the way to achieve high first efficiency and high capacity. The closed pores of the hard carbon porous carbon negative electrode are adjusted in order to reduce the specific surface and improve the first efficiency. However, the temperature for adjusting the closed pores is as high as >1100°C. Patent CN117902577A also has a similar principle. It uses phosphoric acid as an activator and lignin as a carbon source to prepare lignin-based hard carbon materials through low-temperature carbonization, water washing, drying, and high-temperature carbonization. A porous carbon with micropores as the main component can be prepared by low-temperature carbonization of a mixture of phosphoric acid and lignin. During the high-temperature carbonization process, with the rearrangement of carbon crystallites and the growth of carbon layers, the micropores will close to form a rich closed-pore structure in the hard carbon. Closed-pore porous carbon is also prepared by traditional template methods. For example, in patent CN114792782A, silicon dioxide is used as a pore template to prepare porous carbon, and the pores of the porous carbon include open pores and closed pores. The total number of open pores and the closed pores is 100%, of which the number of open pores accounts for 80%-99.9%. Porous carbon provides a continuous conductive channel for the negative electrode, and the closed pores can buffer part of the volume expansion, while the open pores are used to accommodate nano-silicon materials, and some pores are reserved for further alleviating the volume expansion to ensure the low expansion rate of the material. There are also surface modification and coating methods to achieve the pore closed pore effect, such as patent CN116062734A, which mixes electrostatically treated polyolefins and porous carbon, and sequentially performs pre-oxidation and carbonization to obtain the modified porous carbon material. After modification, the open pores of the porous carbon become closed pores. For example, in patent CN116404128A, a highly closed-pore hard carbon material is prepared by modifying the inner wall of the closed pores with a sodium ion conductor and a metal or a metal salt. The preparation method is to use organic matter or biomass as a raw material to obtain a porous hard carbon precursor by a pyrolysis method, and then deposit the sodium ion conductor, the metal or the metal salt into the open pores of the porous hard carbon precursor, and then carbon-coat the composite material, and obtain an internally modified highly closed-pore porous hard carbon material after heat treatment.
[0006] The strategy of achieving closed pores by high-temperature carbonization rearrangement is certainly useful, but for porous carbon, high temperature will greatly reduce the yield of porous carbon and greatly increase energy consumption. The method of using the template method to achieve closed pores in porous carbon has uniform pore size, which is relatively regular and controllable, but the introduction and removal of the template leads to increased costs and more complicated operation procedures. Therefore, there are still few reports on methods for low-temperature porous carbon pore size sealing with good uniformity. Summary of the invention
[0007] The present invention provides a porous carbon, silicon-carbon negative electrode material, preparation method, pole piece and battery to solve the technical problems of low porous carbon yield and complicated template introduction and removal process in the prior art. The porous carbon obtained by the present invention has a large number of closed pores with small caliber and a pore structure in the shape of a gourd, which is conducive to the subsequent silane gas deposition, electrolyte isolation and silicon expansion inhibition, and can well coordinate the high initial efficiency and high capacity performance of silicon-carbon negative electrode materials.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a porous carbon comprising a carbon skeleton and gourd-shaped pores distributed in the carbon skeleton, wherein the average pore size is 0.05-15 nm and the pore volume is 0.05-2 cm 3 / g.
[0010] In the present invention, the average pore size of the porous carbon may be 0.05-6 nm, preferably 1-5.5 nm, for example, 0.06 nm, 1.22 nm, 1.24 nm, 1.76 nm, 2.22 nm, 2.29 nm, 2.52 nm, 2.87 nm, 3.12 nm, 3.45 nm, 3.64 nm, 4.27 nm, 5.23 nm, 5.64 nm or 12.57 nm.
[0011] In the present invention, the pore volume of the porous carbon can be 0.5-1.9 cm 3 / g, for example 0.06 cm 3 / g, 0.78 cm 3 / g, 0.88 cm 3 / g, 1.06 cm 3 / g, 1.19 cm 3 / g, 1.23 cm 3 / g, 1.33 cm 3 / g, 1.34 cm 3 / g, 1.39 cm 3 / g, 1.45 cm 3 / g, 1.64 cm 3 / g, 1.66 cm 3 / g, 1.68 cm 3 / g or 1.82 cm 3 / g.
[0012] In the present invention, the BET specific surface area of the porous carbon can be 80-3200 m 2 / g, preferably 1200-1800 m 2 / g, for example 100 m2 / g, 1080 m 2 / g, 1101 m 2 / g, 1248 m 2 / g, 1478 m 2 / g, 1543 m 2 / g, 1625 m 2 / g, 1626m 2 / g, 1670 m 2 / g, 1705 m 2 / g, 1750 m 2 / g, 1787 m 2 / g, 1780 m 2 / g, 2095 m 2 / g or 3000 m 2 / g.
[0013] In a second aspect, the present invention provides a method for preparing porous carbon, which comprises the following steps:
[0014] S1. Melting the mixture and filtering it; the mixture comprises asphalt-based porous carbon and asphalt, and the average pore size of the asphalt-based porous carbon is 0.1-20 nm, and the pore volume is 0.1-2 cm 3 / g, the mass content of quinoline insoluble matter in the asphalt is 0.003%-3%;
[0015] S2, carbonizing the solid obtained by filtration in step S1.
[0016] In the present invention, in step S1, the temperature of the melting treatment may be 200-650°C, preferably 300-600°C, such as 250°C, 380°C or 600°C.
[0017] In the present invention, in step S1, conventionally, the atmosphere of the melting treatment is a protective atmosphere, such as nitrogen or an inert gas.
[0018] In the present invention, in step S1, the melting treatment time can be 150-180 min. In the present invention, unless otherwise specified, the high temperature treatment time is calculated from the time when the highest temperature is reached, and the time when the temperature is raised is not included.
[0019] In the present invention, in step S1, the heating rate of the melt treatment may be 2-3°C / min.
[0020] In the present invention, in step S1, the mixture may be dried before the melting process. The temperature of the drying process may be 150-180° C. The time of the drying process may be 30-40 min.
[0021] In the present invention, in step S1, the mass ratio of the asphalt-based porous carbon to the asphalt can be (1-5): (1-10), preferably 1: (0.25-9).
[0022] In the present invention, in step S1, the average pore size of the pitch-based porous carbon may be 0.1-10 nm, preferably 3.2-9 nm, such as 0.11 nm, 3.17 nm, 3.42 nm, 3.64 nm, 6.23 nm, 8.0 nm or 18.43 nm.
[0023] In the present invention, in step S1, the pore volume of the pitch-based porous carbon may be 0.8-1.6 cm 3 / g, for example 0.12cm 3 / g, 0.91 cm 3 / g, 1.41 cm 3 / g, 1.42 cm 3 / g, 1.52 cm 3 / g, 1.53 cm 3 / g or 1.8 cm 3 / g.
[0024] In the present invention, in step S1, the BET specific surface area of the asphalt-based porous carbon can be 200-3200 m 2 / g, preferably 1700-2500 m 2 / g, for example 210 m 2 / g, 1783 m 2 / g, 1912 m 2 / g, 1923 m 2 / g, 2200 m 2 / g, 2409m 2 / g, 3180 m 2 / g.
[0025] In the present invention, in step S1, the D50 of the pitch-based porous carbon may be 10-12 μm.
[0026] In the present invention, in step S1, the mass content of quinoline insoluble matter in the asphalt is preferably 0.03%-2%, such as 0.005%, 0.03% or 2.5%.
[0027] In the present invention, in step S1, the D50 of the asphalt may be 10-12 μm.
[0028] In the present invention, in step S1, the softening point of the asphalt can be 80-100°C.
[0029] In the present invention, in step S1, the coking value of the asphalt may be 25%-30%, for example, 26%.
[0030] In the present invention, in step S2, the temperature of the carbonization treatment may be 550-1250°C, such as 580°C, 950°C or 1200°C.
[0031] In the present invention, in step S2, the carbonization treatment time may be 2-2.5 h.
[0032] In the present invention, in step S2, the heating rate of the carbonization treatment may be 2-6°C / min.
[0033] In the present invention, in step S2, the carbonization treatment may first be heated to 400-450°C, for example, 435°C.
[0034] In a third aspect, the present invention provides porous carbon prepared by the method for preparing porous carbon as described above.
[0035] In a fourth aspect, the present invention provides a silicon-carbon negative electrode material, which includes the porous carbon as described above, and silicon particles and carbon particles distributed in the pores of the porous carbon; the mass ratio of the porous carbon, the silicon particles and the carbon particles is 45: (40-50): (1-10).
[0036] In the present invention, the mass ratio of the porous carbon to the silicon particles may be 1:1.
[0037] In the present invention, the mass ratio of the porous carbon to the carbon particles may be 9:1.
[0038] In a fifth aspect, the present invention provides a method for preparing the silicon-carbon negative electrode material as described above, comprising the following steps: in a protective atmosphere, at 400-600° C., passing a silicon source gas and a carbon source gas through the porous carbon.
[0039] In the present invention, the protective atmosphere refers to a gas that does not participate in the reaction, such as nitrogen or an inert gas.
[0040] In the present invention, the method for preparing the silicon-carbon negative electrode material can be carried out at 500°C.
[0041] In the present invention, the silicon source gas may be SiH4.
[0042] In the present invention, the carbon source gas may be acetylene.
[0043] In the present invention, the silicon source gas and the carbon source gas may satisfy a molar ratio of Si to C of 7: (3-6).
[0044] In the present invention, the method for preparing the silicon-carbon negative electrode material may further include the following steps: subjecting the product to surface passivation treatment in a mixed gas at 300° C. The mixed gas may include CO and an inert gas in a volume ratio of 1:99.
[0045] In a sixth aspect, the present invention provides a pole piece, which includes a coating layer and a current collector, wherein the coating layer includes the silicon-carbon negative electrode material as described above.
[0046] In a seventh aspect, the present invention provides a battery comprising the pole piece as described above.
[0047] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0048] The reagents and raw materials used in the present invention are commercially available.
[0049] The positive and progressive effects of the present invention are:
[0050] (1) The present invention proposes a method for growing closed pores by liquid phase asphalt liquid phase impregnation and low temperature polycondensation, which can achieve the closed pore effect of porous carbon at a temperature of <500°C, and the closed pore ratio can be regulated by controlling the component content of the asphalt, the reaction time, and the reaction temperature;
[0051] (2) The present invention obtains porous carbon with mostly small closed pores and gourd-shaped pores, which is beneficial to the subsequent silane gas deposition, electrolyte isolation and silicon expansion inhibition, and can well coordinate the high initial efficiency and high capacity performance of silicon negative electrode materials. DETAILED DESCRIPTION
[0052] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0053] In the following examples and comparative examples,
[0054] The coking value CV is determined in accordance with GB / T8727-2008, and the quinoline insoluble matter QI is determined in accordance with GB / T2293-2008. % refers to the corresponding mass percentage. The denominators of the coking value and quinoline insoluble matter QI are both asphalt mass. The softening point test standard is determined in accordance with the national standard GB / T2294-2019.
[0055] The closed-cell porous carbon yield refers to the ratio of the mass of closed-cell porous carbon collected after closed-cell treatment to the mass of asphalt-based porous carbon added before treatment, that is, yield = mass of closed-cell porous carbon / mass of asphalt-based porous carbon.
[0056] Example 1
[0057] A porous carbon, silicon-carbon negative electrode material and a preparation method thereof, the specific process is as follows:
[0058] S1. Preparation of asphalt-based porous carbon: high softening point asphalt (softening point SP = 220 ° C, coking value CV = 65%) and pore-forming agent potassium carbonate K2CO3 were mixed in a mass ratio of 1: 1, and then heated from room temperature to 350 ° C at 5 ° C / min in a nitrogen gas flow atmosphere of 0.5 L / min for pre-carbonization for 1 h, and then heated to 950 ° C at 5 ° C / min and maintained for 4 h to obtain asphalt-based porous carbon (particle size D50 = 10 μm, BET specific surface area of 2200 m 2 / g, pore volume = 1.8 cm 3 / g, average pore size = 8.0 nm);
[0059] S2, material mixing: at room temperature, 50 g of medium and low temperature asphalt powder (D50 = 12 μm, softening point SP = 80 ° C, coking value CV = 26%, quinoline insoluble matter QI = 0.03%) was placed in a stainless steel container, and the temperature was raised to 180 ° C, and maintained for 30 min to remove trace moisture, and then 10 g of the asphalt-based porous carbon prepared in step S1 was added to the melted medium and low temperature asphalt for mixing;
[0060] S3, forming closed cells: in a nitrogen atmosphere, the mixed material in step S2 was heated to 380°C at a heating rate of 2°C / min for asphalt thermal reaction, and maintained for 150 min;
[0061] S4, filtering and separating: filtering the solid-liquid mixture in step S3 while it is hot, performing solid-liquid separation on the solid porous carbon and the low-temperature asphalt in the liquid phase, and obtaining asphalt-based porous carbon containing closed pores;
[0062] S5, carbonization molding: the pitch-based porous carbon containing closed pores was heated to 435°C at a rate of 2°C / min under a nitrogen flow rate of 0.25 L / min, pre-carbonized for 0.5 h, and then heated to 950°C at a rate of 6°C / min for high-temperature carbonization. After being maintained for 2 h, closed pore porous carbon was obtained with a yield of 98%;
[0063] S6, silane deposition: 100 g of the closed-cell porous carbon obtained in step S5 was placed in a CVD furnace, and the temperature was raised to 500°C at 5°C / min in a 0.5 L / min nitrogen atmosphere, and then a mixed gas consisting of 70 vol% silane SiH4 and 30 vol% acetylene was introduced at 10 L / min, and the opening of the tail pipe air pressure valve was adjusted to keep the pressure in the furnace at 8 kPa, and the ventilation was continued for 9 hours, so that silicon single substance particles and amorphous carbon particles were continuously nucleated and deposited in the pores of the closed-cell porous carbon, with a silicon content of 50wt%, a carbon content of 5wt%, and a porous carbon skeleton of the external substrate of about 45wt%;
[0064] S7, post-treatment: The CVD furnace was cooled to 300°C, and a mixed gas consisting of 1 vol% CO and 99 vol% argon was introduced at a flow rate of 20 L / min. The gas was continuously ventilated for 1.5 h for surface passivation treatment, and then the temperature was cooled to room temperature. Finally, the material was dispersed, screened, demagnetized, etc. to obtain the silicon-carbon negative electrode material.
[0065] Example 2
[0066] The difference from Example 1 is that in step S1, the softening point of the high softening point asphalt is SP = 120 °C, the coking value CV = 35%; the obtained asphalt-based porous carbon has a D50 of 10 μm and a BET specific surface area of 1923 m 2 / g, pore volume = 1.53 cm 3 / g, average pore size = 3.64 nm. In step S5, the yield of the obtained closed-cell porous carbon is 66%.
[0067] Example 3
[0068] The difference from Example 1 is that in step S1, the softening point of the high softening point asphalt is SP=300°C, the coking value CV=78%; the obtained asphalt-based porous carbon has a D50=10 μm and a BET specific surface area of 1783 m 2 / g, pore volume = 1.42 cm 3 / g, average pore size = 3.42 nm. In step S5, closed-cell porous carbon is obtained with a yield of 95%.
[0069] Example 4
[0070] The difference from Example 1 is that in step S1, the pore-forming agent is KOH, and the obtained asphalt-based porous carbon has a D50 of 10 μm and a BET specific surface area of 2409 m 2 / g, pore volume = 1.52 cm 3 / g, average pore size = 3.17 nm. In step S5, closed-cell porous carbon is obtained with a yield of 85%.
[0071] Example 5
[0072] The difference from Example 1 is that in step S1, the pore-forming agent is H3PO4, and the obtained asphalt-based porous carbon has a D50 of 10 μm and a BET specific surface area of 1912 m 2 / g, pore volume = 0.91 cm 3 / g, average pore size = 6.23 nm. In step S5, closed-cell porous carbon is obtained with a yield of 79%.
[0073] Example 6
[0074] The difference from Example 1 is that in step S2, the quinoline insoluble content of the medium-low temperature asphalt is 0.005wt%, D50=12 μm, softening point SP=80°C, and coking value CV=26%. In step S5, closed-cell porous carbon is obtained with a yield of 42%.
[0075] Example 7
[0076] The difference from Example 1 is that in step S2, the quinoline insoluble content of the medium-low temperature asphalt is 2.5wt%, D50=12 μm, softening point SP=80°C, and coking value CV=26%. In step S5, closed-cell porous carbon is obtained with a yield of 98%.
[0077] Example 8
[0078] The difference from Example 1 is that step S1 is omitted. In step S2, the asphalt-based porous carbon used has a D50 of 10 μm and a BET specific surface area of 210 m 2 / g, pore volume = 0.12 cm 3 / g, average pore size = 0.11 nm. In step S5, closed-cell porous carbon is obtained with a yield of 62%.
[0079] Example 9
[0080] The difference from Example 1 is that step S1 is omitted. In step S2, the asphalt-based porous carbon used has a D50 of 10 μm and a BET specific surface area of 3180 m 2 / g, pore volume = 1.41 cm 3 / g, average pore size = 18.43 nm. In step S5, closed-cell porous carbon is obtained with a yield of 91%.
[0081] Example 10
[0082] The difference from Example 1 is that in step S2, the mass ratio of medium-low temperature asphalt to asphalt-based porous carbon is 9: 1. In step S5, closed-cell porous carbon is obtained with a yield of 55%.
[0083] Embodiment 11
[0084] The difference from Example 1 is that in step S2, the mass ratio of medium-low temperature asphalt to asphalt-based porous carbon is 1:4. In step S5, closed-cell porous carbon is obtained with a yield of 96%.
[0085] Example 12
[0086] The difference from Example 1 is that in step S3, the temperature is raised to 250° C. to carry out a thermal reaction of the pitch. In step S5, closed-cell porous carbon is obtained with a yield of 52%.
[0087] Example 13
[0088] The difference from Example 1 is that in step S3, the temperature is raised to 600° C. for the thermal reaction of the pitch. In step S5, closed-cell porous carbon is obtained with a yield of 94%.
[0089] Embodiment 14
[0090] The difference from Example 1 is that in step S5, the temperature is raised to 580° C. for high-temperature carbonization. In step S5, closed-cell porous carbon is obtained with a yield of 99%.
[0091] Embodiment 15
[0092] The difference from Example 1 is that in step S5, the temperature is raised to 1200°C for high-temperature carbonization, and the heating rate after pre-carbonization is 3°C / min, and closed-cell porous carbon is obtained with a yield of 88%.
[0093] Comparative Example 1
[0094] The main difference from Example 1 is that the temperature increase treatment in step S3 is not performed. The specific process is as follows:
[0095] S1. Preparation of asphalt-based porous carbon: high softening point asphalt (softening point SP = 220 ° C, coking value CV = 65%) and pore-forming agent potassium carbonate K2CO3 were mixed in a mass ratio of 1: 1, and then heated from room temperature to 350 ° C at 5 ° C / min in a nitrogen gas flow atmosphere of 0.5 L / min for pre-carbonization for 1 h, and then heated to 950 ° C at 5 ° C / min and maintained for 4 h to obtain asphalt-based porous carbon (particle size D50 = 10 μm, BET specific surface area of 2200 m 2 / g, pore volume = 1.8 cm 3 / g, average pore size = 8.0 nm);
[0096] S2, material mixing: at room temperature, 50 g of medium and low temperature asphalt powder (D50 = 12 μm, softening point SP = 80 ° C, coking value CV = 26%, quinoline insoluble matter QI = 0.03%) was placed in a stainless steel container, and the temperature was raised to 180 ° C, and maintained for 30 min to remove trace moisture, and then 10 g of the asphalt-based porous carbon prepared in step S1 was added to the melted medium and low temperature asphalt for mixing;
[0097] S3, filtering and separating: filtering the solid-liquid mixture in step S2 while hot, performing solid-liquid separation on the solid porous carbon and the low-temperature asphalt in the liquid phase, and obtaining asphalt-based porous carbon containing closed pores;
[0098] S4, carbonization molding: the pitch-based porous carbon containing closed pores was heated to 435°C at a rate of 2°C / min under a nitrogen flow rate of 0.25 L / min, pre-carbonized for 0.5 h, and then heated to 950°C at a rate of 6°C / min for high-temperature carbonization. After being maintained for 2 h, closed pore porous carbon was obtained with a yield of 3%;
[0099] S5, silane deposition: 100 g of the closed-cell porous carbon obtained in step S5 was placed in a CVD furnace, and the temperature was raised to 500°C at 5°C / min in a 0.5 L / min nitrogen atmosphere, and then a mixed gas consisting of 70 vol% silane SiH4 and 30 vol% acetylene was introduced at 10 L / min, and the opening of the tail pipe air pressure valve was adjusted to keep the pressure in the furnace at 8 kPa, and the ventilation was continued for 9 hours, so that silicon single substance particles and amorphous carbon particles were continuously nucleated and deposited in the pores of the closed-cell porous carbon, with a silicon content of 50wt%, a carbon content of 5wt%, and a porous carbon skeleton of the external substrate of about 45wt%;
[0100] S6. Post-treatment: The CVD furnace was cooled to 300°C, and a mixed gas consisting of 1 vol% CO and 99 vol% argon was introduced at a flow rate of 20 L / min. The gas was continuously ventilated for 1.5 h for surface passivation treatment, and then the temperature was cooled to room temperature. Finally, the material was dispersed, screened, and demagnetized to obtain the silicon-carbon negative electrode material.
[0101] Comparative Example 2
[0102] The main difference from Example 1 is that the high temperature carbonization in step S5 is not performed. The specific process is as follows:
[0103] S1. Preparation of asphalt-based porous carbon: high softening point asphalt (softening point SP = 220 ° C, coking value CV = 65%) and pore-forming agent potassium carbonate K2CO3 were mixed in a mass ratio of 1: 1, and then heated from room temperature to 350 ° C at 5 ° C / min in a nitrogen gas flow atmosphere of 0.5 L / min for pre-carbonization for 1 h, and then heated to 950 ° C at 5 ° C / min and maintained for 4 h to obtain asphalt-based porous carbon (particle size D50 = 10 μm, BET specific surface area of 2200 m 2 / g, pore volume = 1.8 cm 3 / g, average pore size = 8.0 nm);
[0104] S2, material mixing: at room temperature, 50 g of medium and low temperature asphalt powder (D50 = 12 μm, softening point SP = 80 ° C, coking value CV = 26%, quinoline insoluble matter QI = 0.03%) was placed in a stainless steel container, and the temperature was raised to 180 ° C, and maintained for 30 min to remove trace moisture, and then 10 g of the asphalt-based porous carbon prepared in step S1 was added to the melted medium and low temperature asphalt for mixing;
[0105] S3, forming closed cells: heating the mixed materials in step S2 to 380°C at a heating rate of 2°C / min for asphalt thermal reaction, and maintaining the temperature for 150 min;
[0106] S4, filtering and separating: filtering the solid-liquid mixture in step S3 while it is hot, performing solid-liquid separation on the solid porous carbon and the low-temperature asphalt in the liquid phase, and obtaining asphalt-based porous carbon containing closed pores;
[0107] S5, carbonization molding: the pitch-based porous carbon containing closed pores was heated to 435°C at a rate of 2°C / min under a nitrogen flow rate of 0.25 L / min, and pre-carbonized for 0.5 h to obtain closed pore porous carbon with a yield of 98%;
[0108] S6, silane deposition: 100 g of the closed-cell porous carbon obtained in step S5 was placed in a CVD furnace, and the temperature was raised to 500°C at 5°C / min in a 0.5 L / min nitrogen atmosphere, and then a mixed gas consisting of 70 vol% silane SiH4 and 30 vol% acetylene was introduced at 10 L / min, and the opening of the tail pipe air pressure valve was adjusted to keep the pressure in the furnace at 8 kPa, and the ventilation was continued for 9 hours, so that silicon single substance particles and amorphous carbon particles were continuously nucleated and deposited in the pores of the closed-cell porous carbon, with a silicon content of 50wt%, a carbon content of 5wt%, and a porous carbon skeleton of the external substrate of about 45wt%;
[0109] S7, post-treatment: The CVD furnace was cooled to 300°C, and a mixed gas consisting of 1 vol% CO and 99 vol% argon was introduced at a flow rate of 20 L / min. The gas was continuously ventilated for 1.5 h for surface passivation treatment, and then the temperature was cooled to room temperature. Finally, the material was dispersed, screened, demagnetized, etc. to obtain the silicon-carbon negative electrode material.
[0110] The main raw material parameters of some embodiments are as follows
[0111]
[0112] Effect Example 1: Microscopic Characteristics of Closed-Cell Porous Carbon
[0113] 1. Test object: closed-cell porous carbon prepared in Examples 1-15 and Comparative Examples 1-2.
[0114] 2. Test method: BET specific surface area, average pore diameter and pore volume are all tested by nitrogen adsorption and desorption commonly used in the art.
[0115] 3. Test results: see the table below.
[0116]
[0117] It can be seen from the above table that after adding medium and low temperature asphalt, the asphalt-based porous carbon will undergo pore closing and pore shrinkage, effectively reducing the specific surface area and forming closed-pore porous carbon, which helps to improve the primary effect of silicon-carbon negative electrode materials.
[0118] From the comparison of Examples 1-3, it can be seen that the higher the softening point of the high-softening-point asphalt, the higher the yield of the prepared closed-cell porous carbon, but too high a softening point will increase the difficulty of pore formation.
[0119] By comparing Examples 1, 4 and 5, it can be seen that when KOH is used as a pore former, the pore size is microporous, and when H3PO4 is used as a pore former, the pore size is uneven and the specific surface area is small.
[0120] From the comparison of Examples 1, 6 and 7, it can be seen that the higher the quinoline insoluble content of the medium and low temperature asphalt is, the better the closed-cell effect of the closed-cell porous carbon is, and vice versa.
[0121] From the comparison of Examples 1, 10 and 11, it can be seen that in the asphalt-based porous carbon and the medium- and low-temperature asphalt, the more asphalt-based porous carbon there is, the worse the closed-cell effect is, and vice versa.
[0122] From the comparison of Examples 1, 12, 13 and Comparative Example 1, it can be seen that the higher the thermal reaction temperature of the asphalt is, the better the closed-cell effect of the closed-cell porous carbon is, but the corresponding specific surface area will also be greatly reduced, which is not conducive to the deposition of silicon.
[0123] From the comparison between Examples 1, 14, 15 and Comparative Example 2, it can be seen that high-temperature carbonization is beneficial to carbon enrichment and performance improvement of silicon-carbon negative electrode materials, but if the temperature is too high, the specific surface area of the closed-cell porous carbon will be too small and the yield will be reduced.
[0124] Effect Example 2: Electrochemical Performance of Silicon Carbon Anode Materials
[0125] 1. Test object: silicon-carbon negative electrode materials prepared in Examples 1-15 and Comparative Examples 1-2.
[0126] 2. Test method:
[0127] (1) Half-cell assembly: The silicon-carbon negative electrode material, conductive agent SP, binder PAA and binder SBR were homogenized in a mass ratio of 95.5: 1.5: 1.5: 1.5, and then the slurry was coated on the copper foil by the doctor blade method with a coating thickness of 240 μm. The coated copper foil was then placed in a vacuum oven at 80°C and dried for 12 h. The dried copper foil was cut into discs with a diameter of 14 mm to make pole pieces. At room temperature, a metal lithium sheet was used as the negative electrode (counter electrode), the pole piece prepared above was used as the working electrode, a polypropylene diaphragm was used, and a 1 mol / L LiPF6 solution was used as the electrolyte (the solvent was ethylene carbonate EC, methyl pyruvate MC and dimethyl carbonate DMC in a volume ratio of 1: 1: 1). The CR2032 button cell was assembled in a vacuum glove box and tightly mechanically sealed.
[0128] (2) Electrochemical performance test: The assembled button cell was left at room temperature for 24 h before the electrochemical test was started. Constant current charge and discharge experiments were carried out in the LAND battery test system. The capacity first efficiency test process was as follows: the charge and discharge voltage window was 0-1.5 V, and the two-step discharge was 0.1 C discharge to 0.01 V, 0.02 C discharge to 0.005 V, and then 0.1 C charge to 1.5 V.
[0129] 3. Test results:
[0130] The discharge (lithium insertion) capacity is measured by discharging at a constant current of 0.1 C to 0.01 V and then discharging at 0.02 C to 5 mV.
[0131] The charging (de-lithiation) capacity is the capacity measured when charged to 1.5 V at a constant current of 0.1 C;
[0132] First effect = charging (lithium removal) capacity / discharging (lithium insertion) capacity;
[0133] See the table below for details.
[0134]
[0135] It can be seen from the above table that the higher the closed-cell porous carbon ratio is, the higher the capacity of the silicon-carbon material obtained after silicon deposition, but the initial efficiency will be reduced.
Claims
1. A porous carbon, characterized in that: It includes a carbon skeleton and gourd-shaped pores distributed in the carbon skeleton, with an average pore diameter of 0.05-15 nm and a pore volume of 0.05-2 cm 3 / g.
2. The porous carbon according to claim 1, characterized in that It meets at least one of the following conditions: (1) The average pore size of the porous carbon is 0.05-6 nm, preferably 1-5.5 nm, such as 0.06 nm, 1.22 nm, 1.24 nm, 1.76 nm, 2.22 nm, 2.29 nm, 2.52 nm, 2.87 nm, 3.12 nm, 3.45 nm, 3.64 nm, 4.27 nm, 5.23 nm, 5.64 nm or 12.57 nm; (2) The pore volume of the porous carbon is 0.5-1.9 cm 3 / g, for example 0.06 cm 3 / g, 0.78 cm 3 / g, 0.88 cm 3 / g, 1.06 cm 3 / g, 1.19 cm 3 / g, 1.23 cm 3 / g, 1.33 cm 3 / g, 1.34 cm 3 / g, 1.39 cm 3 / g, 1.45 cm 3 / g, 1.64 cm 3 / g, 1.66 cm 3 / g, 1.68 cm 3 / g or 1.82 cm 3 / g; (3) The BET specific surface area of the porous carbon is 80-3200 m 2 / g, preferably 1200-1800 m 2 / g, for example 100m 2 / g, 1080 m 2 / g, 1101 m 2 / g, 1248 m 2 / g, 1478 m 2 / g, 1543 m 2 / g, 1625 m 2 / g, 1626 m 2 / g, 1670m 2 / g, 1705 m 2 / g, 1750 m 2 / g, 1787 m 2 / g, 1780 m 2 / g, 2095 m 2 / g or 3000 m 2 / g.
3. A method for preparing porous carbon, characterized in that: It includes the following steps: S1. Melting the mixture and filtering it; the mixture comprises asphalt-based porous carbon and asphalt, and the average pore size of the asphalt-based porous carbon is 0.1-20 nm, and the pore volume is 0.1-2 cm 3 / g, the mass content of quinoline insoluble matter in the asphalt is 0.003%-3%; S2, carbonizing the solid obtained by filtration in step S1.
4. The method for preparing porous carbon according to claim 3, characterized in that: It meets at least one of the following conditions: (1) In step S1, the temperature of the melt treatment is 200-650°C, preferably 300-600°C, for example 250°C, 380°C or 600°C; (2) In step S1, the atmosphere of the melt treatment is a protective atmosphere, such as nitrogen or an inert gas; (3) In step S1, the melting treatment time is 150-180 min; (4) In step S1, the heating rate of the melt treatment is 2-3°C / min; (5) In step S1, the mixture is dried before the melting process; the temperature of the drying process is preferably 150-180°C; the time of the drying process is preferably 30-40 min; (6) In step S1, the mass ratio of the asphalt-based porous carbon to the asphalt is (1-5): (1-10), preferably 1: (0.25-9); (7) In step S1, the average pore size of the pitch-based porous carbon is 0.1-10 nm, preferably 3.2-9 nm, such as 0.11 nm, 3.17 nm, 3.42 nm, 3.64 nm, 6.23 nm, 8.0 nm or 18.43 nm; (8) In step S1, the pore volume of the asphalt-based porous carbon is 0.8-1.6 cm 3 / g, for example 0.12 cm 3 / g, 0.91 cm 3 / g, 1.41 cm 3 / g, 1.42 cm 3 / g, 1.52 cm 3 / g, 1.53 cm 3 / g or 1.8 cm 3 / g; (9) In step S1, the BET specific surface area of the pitch-based porous carbon is 200-3200 m 2 / g, preferably 1700-2500m 2 / g, for example 210 m 2 / g, 1783 m 2 / g, 1912 m 2 / g, 1923 m 2 / g, 2200 m 2 / g, 2409 m 2 / g, 3180 m 2 / g; (10) In step S1, the D50 of the pitch-based porous carbon is 10-12 μm; (11) In step S1, the mass content of quinoline insoluble matter in the asphalt is 0.03%-2%, for example, 0.005%, 0.03% or 2.5%; (12) In step S1, the D50 of the asphalt is 10-12 μm; (13) In step S1, the softening point of the asphalt is 80-100°C; (14) In step S1, the coking value of the asphalt is 25%-30%, for example, 26%; (15) In step S2, the temperature of the carbonization treatment is 550-1250°C, for example, 580°C, 950°C or 1200°C; (16) In step S2, the carbonization treatment time is 2-2.5 h; (17) In step S2, the heating rate of the carbonization treatment is 2-6°C / min; (18) In step S2, the carbonization treatment is first heated to 400-450°C, for example, 435°C.
5. A porous carbon prepared by the method for preparing porous carbon as claimed in claim 3 or 4.
6. A silicon-carbon negative electrode material, characterized in that: It comprises the porous carbon as claimed in claim 1, 2 or 5, and silicon particles and carbon particles distributed in the pores of the porous carbon; the mass ratio of the porous carbon, the silicon particles and the carbon particles is 45: (40-50): (1-10); Preferably, the mass ratio of the porous carbon to the silicon particles is 1:1; Preferably, the mass ratio of the porous carbon to the carbon particles is 9:
1.
7. A method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: It includes the following steps: A silicon source gas and a carbon source gas are passed through the porous carbon at 400-600° C. under a protective atmosphere.
8. The method for preparing the silicon-carbon negative electrode material according to claim 7, characterized in that: It meets at least one of the following conditions: (1) The protective atmosphere is nitrogen or an inert gas; (2) The method for preparing the silicon-carbon negative electrode material is carried out at 500°C; (3) The silicon source gas is SiH4; (4) The carbon source gas is acetylene; (5) The silicon source gas and the carbon source gas satisfy a molar ratio of Si to C of 7:(3-6); (6) The method for preparing the silicon-carbon negative electrode material further comprises the following steps: subjecting the product to surface passivation treatment in a mixed gas at 300°C; the mixed gas preferably comprises CO and an inert gas in a volume ratio of 1:
99.
9. A pole piece, characterized in that: It comprises a coating layer and a current collector, wherein the coating layer comprises the silicon-carbon negative electrode material as claimed in claim 6.
10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Lignin-based hard carbon material, preparation method thereof and application of lignin-based hard carbon material in sodium-ion battery
CN117902577A
Pitch-based porous carbon material and preparation method thereof, silicon-carbon negative electrode material and secondary battery
CN109065861A
Preparation method of novel silicon-carbon negative electrode material and product thereof
CN116613299A
Preparation method of asphalt-based silicon-carbon negative electrode material for lithium ion battery and product of asphalt-based silicon-carbon negative electrode material
CN116730322A
Method for preparing sodium-ion battery hard carbon negative electrode material through porous carbon modification and application of sodium-ion battery hard carbon negative electrode material
CN119018878A
Cited By
Preparation method of pitch-based porous carbon for high-performance silicon carbon
CN120922872A
A method for preparing pitch-based porous carbon for high-performance silicon-carbon applications
CN120922872B
High-performance asphalt-based porous carbon as well as preparation method and application thereof
CN121020582A
High performance pitch-based porous carbon, and preparation method and application thereof
CN121020582B
Non-activation low-cost high-magnification asphalt-based porous carbon as well as preparation method and application thereof
CN121085251A